Investigating diagnostic bias in autism spectrum conditions: An item response theory analysis of sex bias in the AQ‐10. Issue 5 (28th November 2016) - Murray, Aja Louise; Allison, Carrie; Smith, Paula L.; Baron‐Cohen, Simon; Booth, Tom; Auyeung, Bonnie
Abstract : Diagnostic bias is a concern in autism spectrum conditions (ASC) where prevalence and presentation differ by sex. To ensure that females with ASC are not under‐identified, it is important that ASC screening tools do not systematically underestimate autistic traits in females relative to males. We evaluated whether the AQ‐10, a brief screen for ASC recommended by the National Institute of Clinical Excellence in cases of suspected ASC, exhibits such a bias. Using an item response theory approach, we evaluated differential item functioning and differential test functioning. We found that although individual items showed some sex bias, these biases at times favored males and at other times favored females. Thus, at the level of test scores the item‐level biases cancelled out to give an unbiased overall score. Results support the continued use of the AQ‐10 sum score in its current form; however, suggest that caution should be exercised when interpreting responses to individual items. The nature of the item level biases could serve as a guide for future research into how ASC affects males and females differently. Autism Res 2017, 10: 790–800 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.